A Survey of ASAM Members' Knowledge, Attitudes, and Practices in Urine Drug Testing. Issue 5 (October 2015) - Kirsh, Kenneth L.; Baxter, Louis E.; Rzetelny, Adam; Mazuk, Molly; Passik, Steven D.
<x xml:space="preserve">Abstract</x> Objectives: Urine drug testing (UDT) can play an important role in addiction medicine. Indeed, the American Society of Addiction Medicine (ASAM) recently released a white paper, detailing the history of UDT, emphasizing recent advances in the laboratory and clinical science of UDT, and discussed the potential for broadening clinical utility of UDT. We conducted a survey of ASAM members to better understand their knowledge, attitudes, and practices with regard to UDT. Methods: ASAM leadership along with clinical and laboratory experts developed a large pool of items on knowledge, attitudes, and practices around the use and implementation of UDT. These were condensed and converted to a web-based format. Two mass e-mails were sent for recruitment to the survey, with the first e-mail resulting in an open rate of 37% and the follow-up e-mail having an open rate of 34%. Results: A total of 365 respondents completed the survey, with 51% indicating they were Board Certified in Addiction Medicine/Addiction Psychiatry. Up to 93% of respondents indicated they were waivered to prescribe buprenorphine, and 20% indicated that they were certified as a Medical Review Officer (MRO). A total of 93% felt confident in their ability to interpret the results of UDT, 90% used UDT to monitor both medication and illicit substance use, and 79% either agreed (48%) or strongly agreed (31%) with the statement "it is important to do adulteration testing for aberrant behavior." Urine drug testing was most likely to be ordered "when a patient is demonstrating problematic behavior" (70%), and for "baseline testing for new patients plus random selection of current patients" (57%). Significance: The survey revealed that UDT is widely used and highly integrated into the assessment and management of people with addictions undergoing treatment by ASAM members. Greater than 94% of respondents use testing to determine adherence, to monitor abstinence, and to detect an early relapse. The majority felt confident in their ability to interpret and use UDT results, and the vast majority had reportedly used it in changing patient management. Education gaps do exist, however, and should be the focus of future education efforts on UDT.